The effect of salung leaf extract (Psychotria viridiflora) on blood glucose levels in mice - Dara, Niki Dwi Dia; Ruyani, Aceng; Wardana, Rendy Wikrama; Mayub, Afrizal; Karyadi, Bhakti (Universitas Negeri Yogyakarta, 2025)
This research is crucial in the context of the rising global prevalence of diabetes, a metabolic disorder that significantly affects public health. This study aims to determine the effect of salung leaf extract (Psychotria viridiflora) on blood glucose levels in hyperglycemic mice (Mus musculus). The study used 25 mice (Mus musculus) weighing 20-40 grams, divided into 5 treatment groups (P). Each group consisted of 5 mice, including a negative control, positive control, and three experimental groups with the administration of P. viridiflora extract at various doses (0.0112; 0.0225; and 0.0337 g/kgBW). Blood glucose measurements were conducted four times, on days 0, 6, 12, and 18, which included an initial glucose measurement, post-alloxan induction, and subsequent measurements after treatment. Among the three tested doses, the highest dose (0.0337 g/kg BW) proved to be the most effective in reducing blood sugar levels in alloxan-induced M. musculus, with effectiveness comparable to the standard drug Glibenclamide. Thus, the extract of P. viridiflora leaves shows strong potential as an alternative herbal antidiabetic therapy for M. musculus.